Sustainable supply of wood and fibre: does Malaysia have enough - Sahri, Mohd. Hamami (Universiti Putra Malaysia Press, 2008)

(untitled)
Malaysia is the world’s largest exporter of tropical timber (all products), at FOB value of RM 21.5 billion in 2005, followed by Indonesia and Brazil. In 2004, Malaysia overtook Indonesia as the leading exporter of plywood with just over 4.35 million cubic metres (m3 ), but in 2005 China outstripped all producer countries including Malaysia (5.13 million m3) as the largest exporter of tropical plywood. Although the timber industry accounts for less than 3% of total manufactured exports, it has strong industrial linkages integrating about 750 small and medium enterprises (SMEs) with another 1,500 smaller production units. Moreover, this sector is one of the few successful industry clusters developed under the Second Industrial Master Plan. To ensure continuity of sustainable supply of wood and fibres to industries, the government needs to strengthen and harmonize some policies related to: Sustainable Forest Management through: • Better management of forest resources in accordance with the prescriptions given in Forest Management Plans and compliance with SFM (Sustainable Forest Management) requirements et al, in ensuring continuity of log outflow at sustainable levels; • Review cases of harvesting in excess of prescribed allowable cuts, as in Sabah, to ensure reversion to sustainable-level log production; and • Management of log production in the interest of meeting domestic needs especially in log-deficit Sabah, with a view to banning log exports. Forest Plantations, through: • Encouraging private-sector initiatives in forest plantations with financial incentives; • Coordinating and monitoring, nationwide, the progress of forest plantation activities that benefit from Malaysia Plantation Industries Corporation’s (MPIC) assistance programme for forest plantations; and • Permiting agro-forestry practices in forest plantation projects. Biomass Development through: • Intensification of use of non-conventional raw materials (kenaf, oil palm, bamboo, rattan and other non-wood resources), where technically and economically feasible. • Review of the existing R&D policies to encourage more private sector participation in R&D for processing technology and use of non-conventional raw materials. Resource Recycling and Wood Wastes through: • Full utilisation of wood residues from logging and wood-processing industries such as saw-milling and plywood and particle board manufacturing; and • Intensification of use of wood residues generated by management of perennial crop plantations by activities such as pruning and replanting of trees (rubber, coconut, palm oil and crop residues generated by agricultural production); Importation of Raw Materials: • Increase importation of raw materials and components at competitive prices and allow the timber industry to focus on the possibility of producing tertiary products. If all the strategies mentioned above are followed, we believe that the industry has the fundamentals to remain competitive. However, it has to compete with greater intensity to remain ahead in the increasingly competitive world market. The timber sector has a lot to contribute to the national economy, in return for the supportive services that it has received from the government.